Developed Digital Supplementary Material: Learning Backlog Intervention in Grade 9 Mathematics Lessons - Ravalo, Praisel V.; Flores, Jollard S. (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This study would like to address the challenge of curriculum completion within prescribed timeframes, particularly in the context of unforeseen disruptions that result in learning backlogs. Employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design model, the research developed a digital supplementary material (DSM) aimed at mitigating these backlogs in Grade 9 Mathematics. The analysis phase involved surveying 14 Grade 9 Mathematics teachers during the 2023-2024 school year to identify specific content areas affected by incomplete instruction; findings indicated that only 28.6% of classes completed all lessons, with the majority failing to cover fourth quarter topics, notably trigonometry. Guided by these insights, the DSM was designed and developed to directly address the identified gaps. The material underwent expert validation by three mathematics educators, who evaluated it for content accuracy, construct validity, criterion alignment, accessibility, and reliability, resulting in a high overall validity score of 3.47. Subsequently, the DSM was implemented with 87 Grade 10 students who had previously experienced learning backlogs. Quantitative analysis using a paired samples t-test revealed a significant improvement in student performance, with a mean score increase of 2.98 points from pretest to posttest. These results demonstrate the efficacy of the ADDIE-based digital supplementary material in addressing instructional gaps and enhancing learning outcomes in mathematics education.